Recent Progresses in Electrochemical DNA Biosensors for SARS-CoV-2 Detection - Mei, Yanqiu; Lin, Xiaofeng; He, Chen; Zeng, Weijia; Luo, Yan; Liu, Chenghao; Liu, Zhehao; Yang, Min; Kuang, Ying; Huang, Qitong (Frontiers in Bioengineering and Biotechnology, 2022)
The new coronavirus (COVID-19) is still a major public health concern in many nations today. COVID-19 transmission is now controlled mostly through early discovery, isolation, and therapy. Because of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the contributing factor of COVID-19, establishing timely, sensitive, accurate, simple, and budget detection technologies for the SARS-CoV-2 is urgent for epidemic prevention. Recently, several electrochemical DNA biosensors have been developed for the rapid monitoring and detection of SARS-CoV-2. This mini-review examines latest improvements in the detection of SARS-COV-2 utilizing electrochemical DNA biosensors. Meanwhile, this mini-review summarizes the problems faced by the existing assays and puts an outlook on future trends in the development of new assays for SARS-CoV-2, to provide researchers with a borrowing role in the generation of different assays.